Optimalisasi Kapasitas Penggunaan Lahan Parkir Masjid Jami Tangkuban Perahu Setiabudi Jakarta - Baiezt, Ivan Zubeil; Akbardin, Juang; Maknun, Johar (Jurnal Talenta Sipil, 2024)
The need for parking space in the land use planning system for congregational activities becomes very important along with the increasing number of vehicle users. Mosque areas with dense activity centers require sufficient parking space to facilitate access. The mosque congregation's activity center in the Tangkuban Perahu mosque activity zone requires easy access. to the parking lot. The activity system of congregational activities with high physical activity requires an assessment of parking needs in accordance with the activity system. Analyzing parking space requirements based on system performance is the main objective of this research. In particular, the research objective is based on analyzing parking duration. Frequency and accumulation Vehicles in the parking area are a typical impact of the mosque congregation's activity system. The analysis method based on parking space units is analyzed based on the parking method with variables that influence vehicle use in the activity system in the sports activity zone. Parking user characteristic variables are based on vehicle user survey responses from the activity system.